The effects of classical music, rock music, and Qur'an recitation on pregnant mice (Mus musculus) and the development of fetal cerebrum - Arsika, Dwi Yulia Eva; Suarni, Ni Made Rai; Suaskara, Ida Bagus Made (Jurnal Biologi Udayana; Vol 28 No 2 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i02.p07, 2025)
Brain development in fetal mice ( Mus musculus ) within the mother's uterus can be influenced by various factors, including sound (music). Different genres of music may have diverse effects on the brain development of fetal mice. This study seeks to evaluate the impact of classical music, rock music, and Al-Qur'an recitation (murottal) on pregnant mice, focusing on the development of the cerebrum in fetal mice. The research design employed is a Completely Randomized Design (CRD) with four treatment groups: control (K0), classical music (K1), rock music (K2), and Al-Qur'an recitation (K3), each with six replicates. Parameters observed include cerebrum weight, the number of pyramidal cells, and neuroglia. Observations were made using a light microscope equipped with Optilab, with each preparation observed in five fields of view. Data that are normally distributed and homogeneous were analyzed using ANOVA, followed by Duncan's test. For data that are normally distributed but not homogeneous, as well as data that are not normally distributed but homogeneous, the Kruskal-Wallis test was used, followed by the Mann-Whitney test. The results showed that the optimum music stimulation to increase the number of pyramidal cells and neuroglia in the development of the cerebrum of fetal mice was Al-Qur'an recitation (K3) and classical music (K1).